On Linkages and Leakages: Measuring the Secondary Effects of Tourism - Lejarranga, Iza (2012)
Tourism multipliers are widely used tools of services trade analysis. Yet, their derivation and interpretation has often been inconsistent and confusing. This article presents a unifying approach for calculating indicators of tourism linkages and leakages, derives these multipliers for a large sample of more than 150 countries and statistically assesses the relationship among the multipliers, along with several other economic indicators. Contrary to widely held views, the multipliers for tourism linkages and leakages are noncomplementary, as they are based on different economic concepts, so that no particular correlation is to be expected. This independence is confirmed in the empirical cross-country analysis. Moreover, the analysis finds a positive association between the degree of linkages and per-capita income, trade openness and the friendliness of the business climate.